G Protein-coupled pH-sensing Receptor OGR1 Is a Regulator of Intestinal Inflammation. Issue 6 (June 2015) - de Vallière, Cheryl; Wang, Yu; Eloranta, Jyrki J.; Vidal, Solange; Clay, Ieuan; Spalinger, Marianne R.; Tcymbarevich, Irina; Terhalle, Anne; Ludwig, Marie-Gabrielle; Suply, Thomas; Fried, Michael; Kullak-Ublick, Gerd A.; et al.
Abstract : Background: A novel family of proton-sensing G protein-coupled receptors, including OGR1, GPR4, and TDAG8, was identified to be important for physiological pH homeostasis and inflammation. Thus, we determined the function of proton-sensing OGR1 in the intestinal mucosa. Mtehods: OGR1 expression in colonic tissues was investigated in controls and patients with IBD. Expression of OGR1 upon cell activation was studied in the Mono Mac 6 (MM6) cell line and primary human and murine monocytes by real-time PCR. Ogr1 knockout mice were crossbred with Il-10 deficient mice and studied for more than 200 days. Microarray profiling was performed using Ogr1 −/− and Ogr1 +/+ (WT) residential peritoneal macrophages. Results: Patients with IBD expressed higher levels of OGR1 in the mucosa than non-IBD controls. Treatment of MM6 cells with TNF, led to significant upregulation of OGR1 expression, which could be reversed by the presence of NF-κB inhibitors. Kaplan–Meier survival analysis showed a significantly delayed onset and progression of rectal prolapse in female Ogr1 −/− / Il-10 −/− mice. These mice displayed significantly less rectal prolapses. Upregulation of gene expression, mediated by OGR1, in response to extracellular acidification in mouse macrophages was enriched for inflammation and immune response, actin cytoskeleton, and cell-adhesion gene pathways. Conclusions: OGR1 expression is induced in cells of human macrophage lineage and primary human monocytes by TNF. NF-κB inhibition reverses the induction of OGR1 expression by TNF. OGR1 deficiency protects from spontaneous inflammation in the Il-10 knockout model. Our data indicate a pathophysiological role for pH-sensing receptor OGR1 during the pathogenesis of mucosal inflammation. Abstract : Article first published online 7 April 2015.Supplemental Digital Content is Available in the Text.